Radioisotopic purity and imaging properties of cyclotron-produced 99mTc using direct 100Mo(p, 2n) reaction. (19th September 2018) - Uzunov, N M; Melendez-Alafort, L; Bello, M; Cicoria, G; Zagni, F; De Nardo, L; Selva, A; Mou, L; Rossi-Alvarez, C; Pupillo, G; Di Domenico, G; Uccelli, L; et al.
Abstract: Evaluation of the radioisotopic purity of technetium-99m ( 99m Tc) produced in GBq amounts by proton bombardment of enriched molibdenum-100 ( 100 Mo) metallic targets at low proton energies (i.e. within 15–20 MeV) is conducted. This energy range was chosen since it is easily achievable by many conventional medical cyclotrons already available in the nuclear medicine departments of hospitals. The main motivation for such a study is in the framework of the research activities at the international level that have been conducted over the last few years to develop alternative production routes for the most widespread radioisotope used in medical imaging. The analysis of technetium isotopes and isomeric states ( 9x Tc) present in the pertechnetate saline Na 99m TcO4 solutions, obtained after the extraction/purification procedure, reveals radionuclidic purity levels basically in compliance with the limits recently issued by European Pharmacopoeia 9.3 (2018 Sodium pertechnetate ( 99m Tc) injection 4801–3). Moreover, the impact of 9x Tc contaminant nuclides on the final image quality is thoroughly evaluated, analyzing the emitted high-energy gamma rays and their influence on the image quality. The spatial resolution of images from cyclotron-produced 99m Tc acquired with a mini-gamma camera was determined and compared with that obtained using technetium-99m solutions eluted from standard 99 Mo/ 99m Tc generators. The effect of the increased image background contribution due to Compton-scattered higher-energy gamma rays ( E γ > 200 keV), which could cause image-contrast deterioration, was also studied. It is concluded that, due to the high radionuclidic purity of cyclotron-produced 99m Tc using 100 Mo(p, 2n) 99m Tc reaction at a proton beam energy in the range 15.7–19.4 MeV, the resulting image properties are well comparable with those from the generator-eluted 99m Tc.